Motivasi Kerja sebagai Faktor Pendorong Kinerja Karyawan PT Purnama Sinar Gemilang - Brillian Yogi Al Ghifari; Yazid Jamaludin Al Azhar; Sentot Imam Wahjono (Journal of Innovative and Creativity, 2025)
This study aims to analyze the influence of work motivation on improving employee performance at PT Purnama Sinar Gemilang. Work motivation is one of the key factors determining organizational success, as it directly affects employee productivity, discipline, and responsibility. This research employs a qualitative approach using a case study method. Data collection techniques include in-depth interviews, direct observation, and documentation. Informants were selected purposively, consisting of employees and management involved in operational activities and human resource policies. The results of the study indicate that employee motivation remains fluctuating, influenced by intrinsic factors such as responsibility and pride in the job, as well as extrinsic factors including salary, work environment, and reward systems. These findings support Herzberg's Two-Factor Theory, which states that job satisfaction can be enhanced through a combination of motivator and hygiene factors. Furthermore, work motivation significantly contributes to improving both individual and organizational performance. Motivated employees tend to demonstrate better performance, greater discipline, and stronger enthusiasm in achieving targets. This study recommends the implementation of sustainable motivation strategies, such as recognition of achievements, career development opportunities, and a transparent and fair reward system. Consequently, PT Purnama Sinar Gemilang can foster a work environment that supports optimal performance and continuous productivity growth.